MOTIVATION MODERATES THE EFFECT OF INTERNAL CONTROL SYSTEMS AND BUDGETARY PARTICIPATION ON INDIVIDUAL PERFORMANCE - Dewi, Mertyani Sari (Universitas Pendidikan Ganesha, 2020)
Good governance can be realized by various improvements continuing to be made by the government to achieve high performance by perfecting the overall state administration system. This study aimed at obtaining empirical evidence regarding the influence of the internal control system and participation in preparing budgets on individual performance with motivation as moderating. This study was conducted at 30 Bangli District Regional Organizations (OPD) collected through questionnaires. The samples were 60 people through non-probability sampling. This study was tested using a structural equation model (Structural Equation Modeling-SEM) based on variance or Component-based SEM with a Smart-PLS 3.0 analysis tool. The result showed that the internal control system has a significant positive effect on individual performance. Budgeting participation has a positive effect but not significant on individual performance. The result showed that work motivation can strengthen the internal control system and participation in compiling budgets on individual performance.